(untitled) (Лучшие интеллектуальные исследования, 2024)
Teaching foreign languages in special areas, such as rural communities or regions with specific needs, requires tailored methodologies and resources. This article explores the challenges and strategies associated with language instruction in these settings. It focuses on two main aspects: adapting teaching methods to local contexts and leveraging technology to overcome geographical and resource limitations. The article also highlights the importance of cultural integration to enhance language acquisition.